2002
DOI: 10.1046/j.1365-2591.2002.00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct amplification of rRNA gene sequences for identification of selected oral pathogens in root canal infections

Abstract: Direct molecular approaches appear to be a valuable tool for the rapid and reliable diagnosis of infectious diseases, as well as for research purposes. There was no correlation between target microbial species and symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
2
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 29 publications
(38 reference statements)
1
33
2
8
Order By: Relevance
“…were associated with specific signs and symptoms of endodontic origin such as pain, tenderness to percussion, wet canals, and the presence of purulent exudates. Other studies also detected F. nucleatum in symptomatic cases (7) and flare-ups (8). This species is capable of coaggregating with other oral and endodontic species (9), and it has been suggested that it may act as a bridge between earlier and later colonizers in biofilms (10,11).…”
mentioning
confidence: 82%
“…were associated with specific signs and symptoms of endodontic origin such as pain, tenderness to percussion, wet canals, and the presence of purulent exudates. Other studies also detected F. nucleatum in symptomatic cases (7) and flare-ups (8). This species is capable of coaggregating with other oral and endodontic species (9), and it has been suggested that it may act as a bridge between earlier and later colonizers in biofilms (10,11).…”
mentioning
confidence: 82%
“…This has been confirmed by studies investigating the microbiologic conditions of root canals associated with persistent AP. 36,37 Presence of persistent cultivable bacteria at the time of obturation reduced the treatment success rate from 94% to 68%. 2 Similarly, success rate in teeth with negative cultures before obturation was significantly higher than teeth with positive cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Tannerella.forsythia'nın enfekte kök kanallarında PCR kullanılarak saptanmış prevalansları, çalışmalarda % 4-66 arasında dağılım göstermektedir (1,(5)(6)(7)(8)(9)(10)(11). Bu çalışmada saptanan prevalans % 31 olup aynı PCR tekniği ve örnekleme prosedürü kullanan diğer çalışma-ların bulgularıyla uyum göstermektedir (1,6).…”
Section: Discussionunclassified
“…PCR ile Tannerella forsythia, Treponema denticola, Dialister pneumosintes and Prevotella tannerea gibi mikroorganizmaların kök kanallarında, kültür yön-temleri ile saptanandan çok daha yüksek prevalanslarda bulundukları ortaya çıkmıştır (5,6). PCR kullanılarak yapılan farklı çalışma-larda T.forsythia'nın prevalansı %4-52 arasında değişmektedir (1,(5)(6)(7)(8)(9)(10)(11). Ayrıca bu bakterinin varlığı ile belirli semptomlar arasında bir ilişki-nin bulunup bulunmadığı henüz bir netlik kazanmamıştır.…”
unclassified